POSSIBILITIES OF IMPROVING THE QUALITY AND EFFICIENCY OF EDUCATIONAL SERVICES IN THE COUNTRIES OF HIGHER EDUCATION (World Economics and Finance Bulletin, 2024)
The article describes the improvement of the socio-economic situation of the country by increasing the quality and efficiency of educational services in higher educational institutions, as well as the influence of human capital, information resource centers and the potential of professors and teachers.
Keywords: Educational brand; Human capital; high-tech networks